THE IMPACT OF IMMIGRATION ON LANGUAGE EVOLUTION AND CHANGE: A PSYCHOLINGUISTIC PERSPECTIVE - Ganiev, Akhrorjon (University Research Base, 2024)
This paper explores the multifaceted impact of immigration on language evolution and change, drawing on insights from psycholinguistics, sociolinguistics, and historical linguistics. By examining the cognitive, social, and historical factors at play, we seek to understand how language is shaped and transformed through human migration. The paper begins by discussing the theoretical framework underlying this investigation, including concepts such as language contact, language shift, language borrowing, creolization, and acculturation. Subsequently, it delves into the cognitive factors of language evolution, highlighting the role of language acquisition and use in shaping linguistic structures and patterns. The social factors of language evolution are then explored, focusing on the influence of social status, power dynamics, and attitudes towards different languages. Finally, the historical factors of language evolution are examined, considering the impact of events such as colonization, forced migration, and trade on language contact and change. Overall, this paper aims to contribute to a deeper understanding of the complex interplay between immigration and language evolution.